Review and Evaluation of the Book of Interpretation of the Eleventh Surah from the Holy Quran - Majid Ma'aref; Hossein Taghipour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Holy Qur'an is a knowledgeable and realistic book which, according to Qur'anic verses, narrations and wisdom, need to be elaborated and interpreted. Throughout the history of many commentators, based on the methods, trends, and various interpretive schools, they have interpreted this celestial book. Accordingly, the Qur'an's interpretation has evolved, and until the present day complete interpretations or some parts of the Qur'an have been written, and the interpretation has continued. Among these, the book "The Interpretation of the Eleventh Surah from the Holy Qur'an" by Mr. Dharullah Mashayekhi, has been compiled for the course of the disciplinary interpretation of the Qur'anic verses and the theology of theology. In this article, the advantages and disadvantages of this book are criticized and evaluated in terms of its form and content. Due to the existing deficiencies, it is suggested that these comments be applied in the coming editions of the book as the source of the course of interpretive interpretation in the baccalaureate.